Determinan Persalinan Sectio Caesarea di RS Bhayangkara Polda DIY - Widiawati Widiawati; Riska Ismawati H; Mia Dwi Agustiani (Malahayati Nursing Journal, 2026)
ABSTRACT In Indonesia, the cesarean section (CS) delivery rate reaches 25.9%, with the Special Region of Yogyakarta (DIY) ranking third highest at 38.1%. At Bhayangkara Police Hospital DIY, the trend of CS delivery continues to rise annually, primarily due to pathological factors during pregnancy. This study aimed to identify the determinants associated with CS delivery at the hospital. A cross-sectional study was conducted using total sampling of 389 medical records of mothers who delivered in 2023–2024. Data were analyzed using univariate, bivariate (Chi-square test), and multivariate (logistic regression) analyses. Most respondents had term pregnancies (90.2%), graduated from senior high school (86.9%), worked as housewives (79.2%), and were covered by the National Health Insurance (96.1%). Significant associations were found between CS history (p=0.000), premature rupture of membranes (p=0.003), and fetal distress (p=0.010) with CS delivery. In contrast, maternal age and parity showed no significant association. Multivariate analysis identified previous CS history as the most dominant factor, with a 6.69-fold increased risk of CS delivery. A history of cesarean section is the strongest determinant of CS delivery. Further research is recommended to expand the study scope and consider alternative research methods. Keywords: Cs, Delivery, Determinant.  ABSTRAK Angka persalinan sectio caesarea (SC) di Indonesia telah melampaui ambang batas WHO (5–15%), dengan prevalensi 25,9%, dan DIY menempati peringkat ketiga tertinggi (38,1%). RS Bhayangkara Polda DIY mencatat tren peningkatan SC setiap tahun.  Mengetahui determinan yang berhubungan dengan persalinan SC di RS Bhayangkara Polda DIY. Penelitian kuantitatif dengan desain cross-sectional menggunakan data rekam medis ibu bersalin periode 2023–2024. Sampel sebanyak 389 orang menggunakan total sampling. Analisis dilakukan dengan uji Chi-square dan regresi logistik. Terdapat hubungan bermakna antara riwayat SC (p=0,000), ketuban pecah dini/KPD (p=0,003), dan gawat janin (p=0,010) dengan kejadian SC. Usia ibu dan paritas tidak berhubungan. Analisis multivariat menunjukkan bahwa riwayat SC adalah faktor paling berpengaruh (RR = 6,69). Riwayat SC merupakan determinan utama persalinan SC. Edukasi dan pendekatan berbasis risiko disarankan untuk menekan angka SC yang tidak terindikasi medis. Kata Kunci: Determinan, Persalinan, sc